2013
DOI: 10.1002/ece3.419
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on potential recruitment in an ecosystem engineer

Abstract: Climate variability and the rapid warming of seas undoubtedly have huge ramifications for biological processes such as reproduction. As such, gametogenesis and spawning were investigated at two sites over 200 km apart on the south coast of Ireland in an ecosystem engineer, the common cockle, Cerastoderma edule. Both sites are classed as Special Areas of Conservation (SACs), but are of different water quality. Cerastoderma edule plays a significant biological role by recycling nutrients and affecting sediment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
(171 reference statements)
3
33
0
Order By: Relevance
“…3(B)) and C. edule (Fig. 3(C)) shows a distribution of the decline and minimal prevalence compatible with the spawning seasons described in the literature for these species (Seed, 1976;Brousseau, 1987b;Guillou et al, 1990;Martínez-Castro and Vázquez, 2012;Morgan et al, 2013). Moreover, Leavitt et al (1990) reported the seasonal cycle of DN prevalence and condition indices in two softshell clam populations; interestingly, though not highlighted in that paper, the minimal values of prevalence detected in late spring/early summer of their second year of study coincided with declines in the condition indices in both studied populations; those declines in condition indices could be indicative of spawning and, thus, it would support the hypothesis of the role played by spawning in the seasonal pattern of DN through its influence over mortality of diseased individuals.…”
Section: Determinant Factors On the Occurrence Of Disseminated Neoplasiasupporting
confidence: 67%
“…3(B)) and C. edule (Fig. 3(C)) shows a distribution of the decline and minimal prevalence compatible with the spawning seasons described in the literature for these species (Seed, 1976;Brousseau, 1987b;Guillou et al, 1990;Martínez-Castro and Vázquez, 2012;Morgan et al, 2013). Moreover, Leavitt et al (1990) reported the seasonal cycle of DN prevalence and condition indices in two softshell clam populations; interestingly, though not highlighted in that paper, the minimal values of prevalence detected in late spring/early summer of their second year of study coincided with declines in the condition indices in both studied populations; those declines in condition indices could be indicative of spawning and, thus, it would support the hypothesis of the role played by spawning in the seasonal pattern of DN through its influence over mortality of diseased individuals.…”
Section: Determinant Factors On the Occurrence Of Disseminated Neoplasiasupporting
confidence: 67%
“…The gametogenic cycle of C. chione described in Portugal reported three spawning peaks and the release of the gametes lasted from January to October. Water temperature and nutrient supply are known to directly affect the physiological status of bivalves, regulating gametogenic cycles and spawning, among other physiological processes (Wilson and Hodgkin 1967, Hilbish and Zimmerman 1988, Gosling 2003, Morgan et al 2013). In agreement with these studies, we found a very strong relationship between the amount of ripe individuals and the water temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cockles have been shown to undergo boom and bust years (Morgan, O'Riordan, & Culloty, 2013) with the dispersal of cockle larvae and recruitment altering between years (Miller, Versace, Matthews, Montgomery, & Bowie, 2013;Morgan et al, 2013). Another explanation of positive F IS could be the Wahlund effect, caused by the presence of substructure within populations.…”
Section: Connectivity Fine-scale Population Structure and Adaptivementioning
confidence: 99%